(untitled) (University Arena, 2025)
Background. Anterior cruciate ligament (ACL) injuries are among the most frequent and functionally limiting conditions in winter sports, particularly in amateur alpine skiing. Due to the high rotational forces and unpredictable terrain, even recreational athletes face significant risk. Additionally, ACL injuries can compromise long-term functionality and affect occupational activities that require prolonged standing or postural stability. Effective surgical intervention and a personalized rehabilitation plan are essential for regaining neuromuscular control and returning to both sport and professional activity. Objectives. This case study aimed to evaluate the functional recovery and neuromuscular symmetry of a 26-year-old female recreational skier and dental practitioner who sustained a complete ACL rupture in the left knee. The study focused not only on achieving a safe return to sport but also on enabling her reintegration into daily professional activity, which involves long hours of standing and maintaining static posture. After ligament reconstruction with a hamstring autograft, the patient followed a structured, 9-month rehabilitation program with progressive goals, from anatomical healing to functional and occupational reintegration. Methods. The protocol was divided into three phases and included mobility exercises, strength training, proprioceptive and neuromuscular control drills. Functional assessments were conducted using biomechanical equipment: Leg Press and Leg Extension (eccentric and isokinetic), execution speed, Drop Jump Test, Stiffness Test, and stabilometric postural evaluation. Data analysis included the Wilcoxon signed-rank test, symmetry index (SI), and coefficient of variation (CV%). Results. The outcomes showed no significant limb differences (p = 0.929), with SI values below 10% in most tests. CV values were lower for strength and slightly higher for speed metrics. Quadriceps circumference increased (+8.9%), and all functional return-to-activity criteria were met. Conclusion. The applied rehabilitation protocol effectively restored neuromuscular symmetry and functional capacity, supporting a confident return to both recreational skiing and physically demanding professional work. Additionally, improvements in joint mobility and dynamic knee stability were essential in facilitating safe reintegration into daily and sport-specific activities.